(untitled) (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2024)
Purpose: NGOs play a crucial role in empowering women, particularly in developing countries like India, where women face significant socio-economic and cultural challenges. This review aims to synthesize and evaluate the literature on how NGOs contribute to women’s empowerment in India, focusing on their diverse interventions and the impact they have on various aspects of women’s lives. Methodology: This literature review employs a thematic approach, systematically analyzing research studies related to NGOs and women’s empowerment. A comprehensive search was conducted in electronic databases including Google Scholar, JSTOR, and ResearchGate, using keywords such as "NGOs," "women’s empowerment," "India," "microfinance," "self-help groups," and "social programs." The review includes findings from multiple studies to provide a holistic understanding of the role and effectiveness of NGOs in this context. Findings: The findings reveal that NGOs significantly impact women’s empowerment by addressing economic, social, and educational barriers. NGOs contribute to economic empowerment through microfinance and self-help groups, facilitate social empowerment by challenging gender norms and providing community support, and enhance educational opportunities. Despite these achievements, challenges such as sustainability, government support, and the need for broader political empowerment remain. The review underscores the necessity for continued research and improved strategies to maximize the benefits of NGO interventions. Originality/Value: The originality and value of this analysis lie in its comprehensive examination of the roles of NGOs and self-help groups (SHGs) in women’s empowerment. Type of Paper: Review-based Analysis.